2014
DOI: 10.1016/j.celrep.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

A Mitochondrial ATP Synthase Subunit Interacts with TOR Signaling to Modulate Protein Homeostasis and Lifespan in Drosophila

Abstract: SUMMARY Diet composition is a critical determinant of lifespan and nutrient imbalance is detrimental health. However, how nutrients interact with genetic factors to modulate lifespan remains elusive. We investigated how diet composition influences mitochondrial ATP synthase subunit d (ATPsyn-d) in modulating lifespan in Drosophila. ATPsyn-d knockdown extended lifespan in females fed low carbohydrate-to-protein (C:P) diets, but not the high C:P ratio diet. This extension was associated with increased resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Inhibition of ATP synthase leads to decreased TOR signaling in mammalian cells, worms, and flies (Chin et al, 2014; Sun et al, 2014). We found that ATP5B knockdown (Figure 4G), treatment with octyl esters of 2-HG (Figure 4H), and IDH1(R132H) mutation (Figure 4I) all decrease the phosphorylation of mTOR complex 1 substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of ATP synthase leads to decreased TOR signaling in mammalian cells, worms, and flies (Chin et al, 2014; Sun et al, 2014). We found that ATP5B knockdown (Figure 4G), treatment with octyl esters of 2-HG (Figure 4H), and IDH1(R132H) mutation (Figure 4I) all decrease the phosphorylation of mTOR complex 1 substrates.…”
Section: Resultsmentioning
confidence: 99%
“…In mice with an ETC complex III gene mutation, males have reduced life span, whereas females show a subset with increased life span [131]. Drosophila studies have identified many QTLs and genes with sex-specific and sexually-antagonistic effects on aging and mitochondrial function [73, 110, 132136]. For example, Drosophila p53 exhibits developmental stage-specific and sex-specific effects on adult life span indicative of SAP [137], and these effects are modulated in a sex-specific way by foxo [82, 138].…”
Section: Genes With Sexual Antagonistic Pleiotropy (Sap)mentioning
confidence: 99%
“…Our finding that the well-established complex V inhibitor oligomycin in fact promotes hair regeneration suggested that possibly, as in lifespan regulation, mild mitochondrial inhibition may prove to be beneficial. Since mitochondrial complex V acts upstream of TOR from C. elegans to Drosophila and humans (Chin et al, 2014;Sun et al, 2014;Fu et al, 2015), and autophagy is induced both by mitochondrial complex V inhibition ( Figure 1D) and by TOR inhibition ( Figure 2C) (see also (Chin et al, 2014)), we further tested if autophagy induction itself is sufficient for hair regeneration. To this end, we took advantage of a TOR-independent autophagy inducing small molecule, SMER28 (Sarkar et al, 2007).…”
Section: Resultsmentioning
confidence: 99%